Pengaruh Kualitas Pelayanan dan Promosi Terhadap Kepuasan Pelanggan Jasa Transportasi Online Maxim Pada Mahasiswa/I S1 Universitas Bhayangkara Jakarta Raya - Ramadan, Rendy; Sasanti, Ningky; Thamrin, Djuni (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Previous research or related research and previous theoretical studies are very important for research or scientific articles. Relevant and interrelated previous research plays a role in supporting the theory and the relationship or influence between variables. This article reviews the Influence of Service Quality and Promotion on Customer Satisfaction of Maxim Online Transportation Services for Students at Bhayangkara University, Jakarta Raya. This article is a study of management literature. Marketing aims to build a hypothesis that can be used in further research. The implementation of this literature review article is as follows: 1) Service Quality influences Customer Satisfaction; 2) Promotion influences Customer Satisfaction; 3) Service Quality and Promotion have a simultaneous effect on Customer Satisfaction.